EFFECTIVENESS OF CENTELLA ASIATICA EXTRACT ON IL-6 AS BIOLOGICAL MARKER OF POST OPERATIVE WOUND HEALING IN PERIORBITAL REGION: Oral Presentation - Experimental Study - Resident - RATRI PRASETYA NINGRUM N (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Centella asiatica (CA) is considered as major herbal plant that beneficial on wound healing process. Wound healing process will stimulate inflammatory cells to release growth factors and cytokines, e.g., interleukin-6 (IL-6). This aim of this study is to determine the effectiveness of CA on IL-6 levels as a biological marker of postoperative wound healing in the periorbital region. Methods : A double-blind, randomized controlled study on the first day of postoperative periorbital patients was conducted at the Mohammad Hoesin Hospital in Palembang from March to June 2022. There were 30 patients who met inclusion criteria. The effectiveness of CA and placebo were analyzed using Wilcoxon test, while comparisons of the effectiveness were analyzed using Mann-Whitney test (SPSS ver. 22.0). Results : No difference in age, sex, and IL-6 levels before treatment between the CA and placebo groups (p>.05). There was a decrease in IL-6 levels before and after CA administration (p=.005). There was an increase in IL-6 levels before and after giving placebo (p=.031). There was a difference in IL-6 levels between the CA and placebo groups (p=.004) after the intervention. Conclusion : There is a difference in IL-6 levels after administration of systemic centella asiatica on periorbital postoperative wound healing in the first week.